RELIGIOUS EDUCATION AMID THE CHALLENGES OF RELIGIOUS RADICALISM - Ahmad Asroni (LPPM STAIS Dharma Indramayu, 2021)
Abstract This article discusses the importance and urgency of the implementation of multicultural religious education. It can be used as an effective instrument and media to reduce religious radicalism and terrorism in Indonesia. Multicultural religious education provides the same space for the growth of differences and religious diversity. Through multicultural religious education, students are expected to have a high commitment to their religion while having a tolerance and appreciative attitude towards other religions. With a multicultural religious education, students are expected to have a sense of plurality. It will only be successful if it is taught by educators who have multicultural awareness. In addition, the curriculum, materials, methods, and evaluation of multicultural religious education learning must also contain and be compatible with multicultural values. Therefore, it needs political will from all stakeholders to jointly formulate a blueprint for multicultural religious education. Keywords: multicultural religious education, religious radicalism, terrorism, student Abstrak Artikel ini membahas tentang pentingnya dan urgensi penyelenggaraan pendidikan agama multikultural. Ini dapat digunakan sebagai instrumen dan media yang efektif untuk mengurangi radikalisme agama dan terorisme di Indonesia. Pendidikan agama multikultural memberikan ruang yang sama bagi tumbuhnya perbedaan dan keragaman agama. Melalui pendidikan agama multikultural, peserta didik diharapkan memiliki komitmen yang tinggi terhadap agamanya sekaligus memiliki sikap toleransi dan apresiasi terhadap agama lain. Dengan pendidikan agama multikultural diharapkan siswa memiliki rasa pluralitas. Hal itu hanya akan berhasil jika diajarkan oleh pendidik yang memiliki kesadaran multikultural. Selain itu, kurikulum, materi, metode, dan evaluasi pembelajaran pendidikan agama multikultural juga harus memuat dan selaras dengan nilai-nilai multikultural. Oleh karena itu, diperlukan political will dari seluruh stakeholder (pemangku kepentingan) untuk bersama-sama merumuskan blueprint pendidikan agama multikultural. Kata kunci: Pendidikan agama multikultural, radikalisme agama, terorisme, peserta didik